Carbon Pricing for Low-Carbon Investment - Karsten Neuhoff (Climate Policy Initiative, 2011)
The EU European Trading Scheme (EU ETS) started operating in 2005 and was established with the EU Climate Package of 2008 as a permanent mechanism for Europe. Now in its second phase, policymakers are evaluating its success to date and considering next steps for its evolution. With the ultimate goal of a low-carbon economy, key questions have been: does the ETS facilitate a shift from carbon-intensive investments to low-carbon investments? What improvements can policymakers apply to accelerate low-carbon investment? To answer these questions, Climate Policy Initiative (CPI) and Climate Strategies conducted a multiinstitute analytical project, “Carbon Pricing for Low-Carbon Investment” from February to December 2010. Led by CPI Berlin director Karsten Neuhoff, participating organizations included London School of Economics, DIW Berlin, ETH-Zürich, ISI-Fraunhofer, Universidad Carlos III de Madrid and University of Erlangen-Nürnberg. Studies in the project include the following: Climate Change, Investment and Carbon Markets and Prices – Evidence from Interviewing Managers Ralf Martin (LSE), Mirabelle Muûls (Imperial College) and Ulrich Wagner (Universidad Carlos III de Madrid) Relative Importance of Different Climate Policy Elements for Corporate Climate Innovation Activities: Findings for the Power Sector Karoline Rogge (ISI Fraunhofer), Tobias Schmidt (ETH Zürich) and Malte Schneider (ETH Zürich) The Role of CDM Post-2012 Alexander Vasa (CPI) and Karsten Neuhoff (CPI) Emissions Trading Schemes under IFRS - Towards a true and fair view Madlen Haupt (CPI) and Roland Ismer (University of Erlangen-Nürnberg) This policy summary describes key findings and implications from the studies included in the project and the workshops hosted in Berlin and Paris. Papers from the studies can be found at www.climatepolicyinitiative.org and www.climatestrategies.org.
Keywords: Q48; L21; O3; 330; Carbon Pricing